Pulmonary adiaspiromycosis in armadillos killed by motor vehicle collisions in Brazil - Pedro Enrique Navas-Suárez; Carlos Sacristán; Josue Díaz-Delgado; Débora R. Yogui; Mario Henrique Alves; Danny Fuentes-Castillo; Catalina Ospina-Pinto; Roberta Ramblas Zamana; Arnaud Leonard Jean Desbiez; Jose Luiz Catão-Dias (Scientific Reports, 2021)
Abstract Knowledge of infectious diseases in wildlife provides important information for preventing potential outbreaks of zoonotic diseases. Adiaspiromycosis is a neglected human disease caused by dimorphic Onygenales fungi. The disease is produced by the inflammatory response against growing adiaspores, leading to granulomatous pneumonia. In humans, adiaspiromycosis is relevant in immunosuppressed patients. In animals, it is associated with pneumonia in fossorial species. Given the potential role of armadillos in the epidemiology of adiaspiromycosis, in this study, we sought to investigate the occurrence and pathological features of adiaspiromycosis in roadkilled armadillos. In total, 54 armadillo carcasses were suitable for postmortem pathologic examinations between February 2017 and 2020. Adiaspores, associated with granulomatous lesions, were observed in ten six-banded (Euphractus sexcinctus) and two southern naked-tailed armadillos (Cabassous unicinctus). A previously uncharacterized Onygenales species was molecularly identified in two E. sexcinctus. In summary, herein we report 12 cases of pulmonary adiaspiromycosis (PA) in two species of free-living armadillos in Brazil. Both, the morphology of the fungus, as well as the histopathological findings (granulomatous inflammatory response to adiaspores) are consistent with PA; however, as the molecular identification differs from the reported species, the potential impact of this fungus for human PA is unknown, and we cannot rule out its impact on public health.